(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
Cross-border companies’ mobility is issue which has been gaining public attention in Europe since the end of the 1980’s. Although it is clear, from the wording of the articles 49 and 54 of the TFEU, that companies should benefit from a freedom of establishment, in practice, the scope of this freedom is quite unclear. Companies wishing to move abroad are usually facing insurmountable obstacles which are still, more than 30 years after the famous Daily Mail case, very present. The recent EU legislative activity may finally bring this problem to an end. In April 2018 the European Commission proposed new rules on cross-border mobility. By enacting the Proposal of the Directive on cross-border conversions, mergers and divisions European Commission introduced important novelties to the cross-border mobility with an aim to simplify procedures, bring legal certainty and create such a legal environment which will enable companies to operate easily on the Single Market. In this paper authors will analyse only the rules of the Proposal that apply to cross- border conversions of companies. The new Proposal on cross-border conversions seem to be an adequate tool for companies that wish to convert abroad. However, the process of conversion is far from being simple. It is a very specific, multi-layered process which involves different stakeholders and authorities and requires their coordinated action. Authors will provide for a critical overview of the proposed legal solutions with special respect to the recent ECJ decision in Polbud case, in which the ECJ reaffirm the right of companies to cross-border conversion.